Jarimah Zina dan Pemerkosaan dalam Qanun Jinayat Aceh: Analisis Perumusan Metode Istinbath - R. Fakhrurrazi (Cyber Media Indonesia, 2020)
This research is an attempt to find out and formulate the method of such used in drafting Qanun Jinayat Aceh in particular about Jarimah (crime) zina and rape. The research on the two networks is limited to three variants, namely definitions, actors, and ‘uqubat. The theory used is the method of such lughawiyah, ta'liliyah, and istislahiyah. The lughawiyah method is reasoning against the evidence by resting on the meaning of harfiyah pronunciation. While the ta'liliyah method is a reasoning method that refers to ' Illat. While the method of Istislahiyah is reasoning that refers to the benefit. The results of this research proved that the formulation of legal norms set in Qanun Jinayat Aceh, especially in the network of zina and rape and three variations can be accountable methodologically. Definition and adultery are formulated using ta'liliyah method with the approach ' Illat tasyri'i. While the ‘uqubat zina is formulated using the method of Lughawiyah with the meaning of mantuq or ibarat an-nash. Then the definition of rape is formulated using the method of Istislahiyah. Whereas rape perpetrators use Lughawiyah method with a mafhum mukhalafah approach. While ' uqubat rape uses the method of Istislahiyyah. DOI: https://doi.org/10.5281/zenodo.3672381